Regulatory mechanism of ABCB1 transcriptional repression by HDAC5 in rat hepatocytes under hypoxic environment - Wei, Ziqin; Mu, Hongfang; Qiu, Fangfang; Zhao, Minghui; Zhang, Xiaojing; Li, Wenbin; Jia, Hai; Wang, Rong (Frontiers in Physiology, 2025)
ObjectivePrevious research has demonstrated that the hypoxic environment at high altitudes significantly alters the pharmacokinetics of many drugs, reducing their efficacy and increasing adverse effects. A key factor in this altered drug metabolism is the inhibition of ATP-binding cassette subfamily B member 1 (ABCB1), an efflux transporter protein, in the liver tissues of plateau rats. Rat ABCB1, encoded by the ABCB1A and ABCB1B genes, has two isoforms functionally analogous to human ABCB1. Histone acetylation, an epigenetic mechanism, may regulate ABCB1 transcription in hypoxic conditions by modifying chromatin structure and interacting with signaling pathways. However, its role in ABCB1 transcriptional regulation under hypoxia remains unclear. Based on this, the present study employed the BRL cell line to establish a hypoxia model, aiming to investigate the histone acetylation-mediated regulatory mechanisms of ABCB1 expression under hypoxic conditions, with the ultimate goal of providing novel theoretical foundations for rational drug use in high-altitude regions.MethodsEstablishment of BRL hypoxia model: BRL cell viability was detected by CCK-8 assay, and HIF-1α expression was measured by RT-qPCR and Western blot. After treating the BRL hypoxia model with HDAC inhibitors, ABCB1 and HDAC5 expression were detected by RT-qPCR, Western blot, and immunofluorescence. Rhodamine 123 accumulation assay was performed to examine the effect of HDAC inhibitors on ABCB1 functional activity. HDAC5 was targeted by siRNA technology to detect ABCB1 and H3K9ac expression. CUT&Tag assay was used to measure H3K9ac levels at the ABCB1 promoter region. After SAHA treatment of the BRL hypoxia model, SP1 expression was detected by RT-qPCR and Western blot. Combined treatment with SAHA and siRNA targeting SP1 was performed to detect ABCB1 expression. Co-immunoprecipitation and fluorescence colocalization assays were conducted to examine interactions among SP1, HDAC5, and ABCB1.ResultsAfter hypoxic culture for different durations, cell viability decreased while HIF-1α expression increased, indicating the successful establishment of the BRL hypoxia model. In the BRL hypoxia model, ABCB1 and SP1 expression decreased while HDAC5 expression increased. After SAHA treatment, ABCB1 and SP1 expression were upregulated while HDAC5 was downregulated. Rhodamine 123 accumulation assay showed that SAHA could enhance ABCB1 functional activity by inducing its expression. After HDAC5 was knocked down using siRNA, ABCB1 and H3K9ac expression increased, and ABCB1 functional activity was enhanced. CUT&Tag assay demonstrated that H3K9ac levels at the ABCB1B promoter region decreased in the BRL hypoxia model, while HDAC5 inhibition increased H3K9ac levels at this region. After SP1 was knocked down using siRNA, the inductive effect of SAHA on ABCB1 was blocked. Co-immunoprecipitation and fluorescence colocalization showed interactions among SP1, HDAC5, and ABCB1.ConclusionIn BRL cells, HDAC5 may be recruited by SP1 to form a complex, reducing free HDAC5, increasing H3K9ac at the ABCB1B promoter, and activating ABCB1 transcription. In the BRL hypoxia model, disruption of the SP1-HDAC5 complex increased free HDAC5, lowered H3K9ac at the ABCB1B promoter, and suppressed ABCB1 transcription. These results suggest that HDAC inhibitors enhance ABCB1 expression in hypoxic environments, indicating that combining HDAC inhibitors with therapeutic agents could mitigate reduced drug efficacy and adverse effects caused by ABCB1 suppression.